Solid particle erosion behaviour and protective coatings for gas turbine compressor blades—a review - Alqallaf, Jasem; Ali, Naser; Teixeira, Joao Amaral; Addali, Abdulmajid (MDPI, 2020)
Gas turbines (GTEs) are often utilised in harsh environments where the GT components, including compressor vanes and rotor blades, are subject to erosion damage by sand and dust particles. For instance, in a desert environment, the rate of damage made by solid particles erosion (SPE) becomes severe, and therefore results in degradation to the GTE parts, lowering the cycle efficiency, reducing the device lifetime, and increasing the overall cost of the operation. As such, understanding the erosion mechanism caused by solid particles and the effects associated with it is crucial for selecting the appropriate countermeasures and maintaining the system performance. This review paper provides a survey of the available studies on SPE effects on GTEs and surface protective coatings. Firstly, the ductile and brittle SPE mechanism is presented, as well as the ductile-brittle transition region. Then, an in-depth focus on the parameters associated with the SPE, such as particles properties and impingement conditions, is introduced. Furthermore, the existing theoretical models are shown and discussed. Afterwards, erosion resistant coating materials for surface protection and their selection criteria are covered in the review. Finally, the gap in knowledge and future research direction in the field of SPE on GTEs are provided.
Keywords: SPE; compressor blades surface; cycle efficiency; erosion models; gas turbine engines